The Influence of 3D Printing on Global Container Multimodal Transport System. (6th November 2017) - Chen, Zhen
Abstract : Container multimodal transport system was an important promoter of postwar globalization. But in the future, part of global manufacturing may change from centralized to distributed due to 3D printing. To evaluate its impact, this research established a system dynamics model of sneakers supply chain firstly. The modeling showed that the total demand of international transport would decline after the application of 3D printing. For consumer country, the return of manufacturing would increase its container business. And that of producer country would reduce correspondingly. But for resource country, its resource exports would decline, while its container business may grow for the local processing of printing filaments. Secondly, the evaluations based on the data of Guangzhou port suggest that the 3D printing of sneakers was not enough to subvert the existing system. It would be broken only after the 3D printing of electrical products. By then, more manufacturing activities would transfer to the end of supply chain. On the other hand, producer country may actively respond to maintain its advantage in incumbent industrial pattern, such as Belt and Road initiative proposed by China. Deglobalization, caused by 3D printing, and globalization strengthening, caused by trade cooperation, will affect this system simultaneously.